Diseño de Balanced Scorecard para aumentar la rentabilidad en la empresa Transportes N&M Moncada S.R.L en el periodo 2015-2016” - Rivero Ríos, Jorge Félix. (2016)
This research project's main objective was to demonstrate that the design of a Balanced Scorecard increase the profitability of the company Transportes N&M Moncada in the period 2015-2016. For this, we used the methodology developed by Robert Kaplan and David Norton, with the active participation of managers and employees of the company, in order to involve all staff from the beginning in the design of this management system, which will deepen the strategy in the short and medium term in all functional areas. After an external and internal analysis of the company, we can identify critical success factors that will enable the achievement of the institutional vision. Then the vision was circulated proposing strategic objectives as 4 BSC perspectives: Financial, Customers, Internal Processes and Learning and Growth. From them, we identify primary and second-level indicators, which allow a closer monitoring for each goal. To measure progress in achieving each indicator, we identified reasonable and possible to achieve strategic goals. To observe the behavior of profitability after designing a BSC for the company, used as sample entries from January to October 2015, offering 3 different scenarios for 2016: Base scenario (increase of 3.8%), conservative scenario (9.4% increase) and an optimistic scenario (15% increase), resulting in only achieve significantly increase profitability if we are in an optimistic scenario, where we meet all the goals of the proposed indicators.